2014
DOI: 10.1111/bph.12756
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of transglutaminase 2 activity in H9c2 cells by PKC and PKA signalling: a role for transglutaminase 2 in cytoprotection

Abstract: BACKGROUND AND PURPOSETissue transglutaminase (TG2) has been shown to mediate cell survival in many cell types. In this study, we investigated whether the role of TG2 in cytoprotection was mediated by the activation of PKA and PKC in cardiomyocyte-like H9c2 cells. EXPERIMENTAL APPROACHH9c2 cells were extracted following stimulation with phorbol-12-myristate-13-acetate (PMA) and forskolin. Transglutaminase activity was determined using an amine incorporating and a protein crosslinking assay. The presence of TG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Our previous studies have shown that TG2 is involved in cytoprotection triggered by PKA and PKC-dependent signalling pathways in H9c2 cells [27]. In the current study the role …”
Section: The Role Of Tg2 In A1 Adenosine Receptor-induced Cell Survivalmentioning
confidence: 60%
See 3 more Smart Citations
“…Our previous studies have shown that TG2 is involved in cytoprotection triggered by PKA and PKC-dependent signalling pathways in H9c2 cells [27]. In the current study the role …”
Section: The Role Of Tg2 In A1 Adenosine Receptor-induced Cell Survivalmentioning
confidence: 60%
“…Protein was determined using the bicinchoninic acid (BCA) protein assay [24], using a commercially available kit (Sigma-Aldrich Co. Ltd), with bovine serum albumin (BSA) as the standard Biotin-labeled cadaverine-incorporation assays were performed according to Slaughter et al. [25] with modifications [26], as described previously [27]. The biotin-labeled peptide cross-linking assay was performed according to the method of Trigwell et al [28] with minor modifications [27].…”
Section: Transglutaminase Activity Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible explanations for this include reversal of amine incorporation by TG (Stamnaes et al 2008), targeting of modified proteins for degradation or their rapid removal from the cell. Our previous studies have reported the rapid expulsion of biotinylated proteins from H9c2 cells following treatment with PMA or forskolin (Almami et al 2014). It could be that the rapid expulsion of biotinylated proteins from N2a cells occurs via exosomes (Kalani et al 2014).…”
Section: In Situ Visualisation Of Tg2 Activitymentioning
confidence: 97%